33.1k views
0 votes
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation.

3x + 2y = −21
x − 3y = 4
A. 3(3y + 4) + 2y = −21
B. 3(−3y + 4) + 2y = −21
C. 3x + 2(3y + 4) = −21
D. 3x + 2(−3y + 4) = −21

User DoctorRu
by
7.2k points

1 Answer

6 votes

Answer:

Option A

Explanation:

Step 1: Naming both equations:


Eq. 1: 3x + 2y=-21\\Eq. 2 : x-3y=4

Step 2: Isolating x in Eq. 2


x=3y+4

Step 3: Replacing x in Eq. 1


3(3y+4)+2y=-21

Therefore, the answer is Option A

User Ben Hyde
by
8.2k points